Electrical Power Quality Analysis In Department Education Mechanical Engineering FT UNY - Bayu Setyo Wibowo; Bagus Tri Kuncoro; Ridha Ulfia Rahmah (Jurnal Teknik Elektro dan Komputer TRIAC, 2026)
The purpose of this research is to determine the electrical load profile and power quality of the power distribution system in the Department of Mechanical Engineering Education, Faculty of Engineering, Yogyakarta State University. The power quality study will provide recommendations for improving one of the electrical parameters, namely the power factor, and compare the measured electrical quantities with existing standards. This electrical power quality analysis was carried out starting with measurements on the electrical panels in the Department of Mechanical Engineering Education, the panels include Fabrication SDP, CNC and lathe machine SDP, welding machine SDP, lighting load and AC load using a power quality analyzer (A3Q) measuring instrument. The measurement data includes apparent power, active power, reactive power, current, voltage, frequency, Current THD, voltage THD, and power factor. The measurement data is then processed into data in the form of a comma-separated values file (csv) which will then be converted into excel data (xls). This conversion data will then be analyzed and then compared with the existing power quality standards. Based on the results of the measurements and analysis carried out, it shows that the overall power factor value on the SDP panel and all loads in the machine direction is still below 0.86 and there is a neutral current caused by an unbalanced load. The largest neutral current value is on the CNC panel, which is 21.46 amperes